Colony Morphology of Yeast Isolates from Tuak and Its Application in Producing Ethanol From Sugarcane Bagasse - Hermansyah Hermansyah; Feggy Arini; Nirwan Syarif; Heni Yohandini (Program Pascasarjana Universitas Sriwijaya, 2016)
Abstract: Colony morphology yeast isolates from tuak and its application in producing ethanol from sugarcane bagasse has been conducted. Yeast isolates used in this work were HT4, HT5, and HT20 obtained from Tuak. These isolates have cream to yellow in color, spherical to oval in shape, and grow as budding cells. Our goal is to find yeast isolates used as microbial agent in fermentation process producing ethanol from lignocellulosic biomass as raw material. Based upon morphology showed that these isolates were Candida species. Isolate HT5 then used to see its potent as agent in bioethanol production. Fermentation of 5 g sugarcane bagasse substrate resulted 0.0008% ethanol. This results indicated that isolate has a potent as microbial agent for fermentation, however the optimum condition of process is needed to furthermore study. Keywords: Candida species, bioethanol, TuakAbstrak (Indonesian): Telah dilakukan penelitian terhadap morfologi koloni dari isolat khamir dari tuak dan aplikasinya dalam produksi etanol dari ampas tebu. Isolat khamir yang digunakan adalah koloni HT4, HT5, dan HT20 yang telah didapat dari tuak. Isolat-isolat ini memiliki bentuk warna krem hingga kuning dengan bentuk bulat hingga oval dan pertumbuhannya dengan membentuk tunas. Tujuannya adalah untuk mendapatkan isolat ini akan digunakan sebagai agen mikroba pada proses fermentasi menghasilkan etanol dari biomasa lignoselulosa sebagai bahan bakunya. Berdasarkan morfologi menunjukan bahwa isolat-isolat ini adalah spesies Candida. Isolat HT5 selanjutnya digunakan untuk melihat potensinya sebagai agen dalam produksi bioetanol. Fermentasi menggunakan 5 g subtrat ampas tebu menghasilkan etanol sebesar 0.0008%. Hasil ini mengindikasikan bahwa isolat memiliki potensi sebagai agen fermentasi menghasilkan etanol akan tetapi masih perlu diteliti lebih lanjut untuk kondisi optimum prosesnya.Kata kunci: spesies Candida, bioetanol. tuak